2021
DOI: 10.3389/fnagi.2021.605158
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Morphological Network Efficiency of Human Brain: Cognitive Intelligence and Emotional Intelligence

Abstract: Network efficiency characterizes how information flows within a network, and it has been used to study the neural basis of cognitive intelligence in adolescence, young adults, and elderly adults, in terms of the white matter in the human brain and functional connectivity networks. However, there were few studies investigating whether the human brain at different ages exhibited different underpins of cognitive and emotional intelligence (EI) from young adults to the middle-aged group, especially in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 120 publications
1
11
0
Order By: Relevance
“…As stated in our previous study (Li et al, 2021 ), the white matter tractography could not reliably quantify long-range structural connectivity (Jeurissen et al, 2019 ) and was largely affected by head motion and might involve a large number of false-positive connections (Thomas et al, 2014 ; Maier-Hein et al, 2017 ); the structural covariance network from a large number of participants only yielded one single correlation matrix but did not reveal individual differences (Alexander-Bloch et al, 2013 ; Li et al, 2021 ). Therefore, in this study we still used macroscale morphology network that was based on distributions of cortical surface characteristics (cortical volume, thickness, and surface area) from resting-state fMRI (Li et al, 2021 ) in order to explore the neural substrates of state and trait anxiety. Corresponding to the temporal variations of human brain functional network, we changed bin number of frequency distributions of cortical surface characteristics (area, thickness, and volume) to explore the spatial variations of brain structural network.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…As stated in our previous study (Li et al, 2021 ), the white matter tractography could not reliably quantify long-range structural connectivity (Jeurissen et al, 2019 ) and was largely affected by head motion and might involve a large number of false-positive connections (Thomas et al, 2014 ; Maier-Hein et al, 2017 ); the structural covariance network from a large number of participants only yielded one single correlation matrix but did not reveal individual differences (Alexander-Bloch et al, 2013 ; Li et al, 2021 ). Therefore, in this study we still used macroscale morphology network that was based on distributions of cortical surface characteristics (cortical volume, thickness, and surface area) from resting-state fMRI (Li et al, 2021 ) in order to explore the neural substrates of state and trait anxiety. Corresponding to the temporal variations of human brain functional network, we changed bin number of frequency distributions of cortical surface characteristics (area, thickness, and volume) to explore the spatial variations of brain structural network.…”
Section: Introductionsupporting
confidence: 66%
“…Corresponding to functional network, we also changed bin number (spatial scales to measure morphological distribution) and gained different morphological similarity resolutions to investigate spatial variations of human brain structural network underlying state and trait anxiety. Previous studies have demonstrated that morphological similarity might be the most accurate and robust method to reflect information transfer between brain regions (Seidlitz et al, 2018 ; Li et al, 2021 ), and different spatial resolutions of measuring morphological similarity could detect spatial robustness of human brain structural network underlying state and trait anxiety. This was the first study to examine spatial robustness of human brain networks and characterized the dependence of topological mechanisms of anxiety on spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations